2017
DOI: 10.1111/nph.14485
|View full text |Cite
|
Sign up to set email alerts
|

Plant, microbial and ecosystem carbon use efficiencies interact to stabilize microbial growth as a fraction of gross primary production

Abstract: The carbon use efficiency of plants (CUE ) and microorganisms (CUE ) determines rates of biomass turnover and soil carbon sequestration. We evaluated the hypothesis that CUE and CUE counterbalance at a large scale, stabilizing microbial growth (μ) as a fraction of gross primary production (GPP). Collating data from published studies, we correlated annual CUE , estimated from satellite imagery, with locally determined soil CUE for 100 globally distributed sites. Ecosystem CUE , the ratio of net ecosystem produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 44 publications
8
67
0
Order By: Relevance
“…There was also consistency in the relative importance of environmental factors controlling MMQ and CUE between this study and Sinsabaugh et al. (). Biological factors, followed by edaphic factors and meteorological factors, were the dominant controls for both MMQ and CUE as shown by SEM.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…There was also consistency in the relative importance of environmental factors controlling MMQ and CUE between this study and Sinsabaugh et al. (). Biological factors, followed by edaphic factors and meteorological factors, were the dominant controls for both MMQ and CUE as shown by SEM.…”
Section: Discussionsupporting
confidence: 84%
“…Our mean MMQ was similar to the microbial respiratory carbon turnover calculated from qCO 2 and CUE using an independent data set (Sinsabaugh et al. ). Theoretically, higher CUE means more carbon is assimilated into microbial biomass, and less carbon enters microbial biomass respire as BR, corresponding to a lower MMQ; lower CUE indicates less carbon is assimilated into microbial biomass and higher MMQ.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, we found that the microbial metabolic quotient (qCO 2 ) was positively related to both R H ‐SOC new and RPE (Figure c). This suggests that an enhanced rhizodeposition by acquisitive species increase microbial allocation of energy to mineralization activities relative to growth (Shahzad et al, ), potentially in relation with a reduction in N availability by enhanced root N uptake, a lower carbon use efficiency and a faster turnover of microbial biomass (Chen et al, ; Sinsabaugh, Moorhead, Xu, & Litvak, ). This variation in microbial activity could also potentially be linked to the selection of rhizosphere microbiomes with contrasting SOC mineralization abilities by plant species with different economic strategies (Pascault et al, ; Schimel & Schaeffer, ).…”
Section: Discussionmentioning
confidence: 99%